Shari’a Stock Zakat: Alternative Financial Inclusion for Empowering Mustaḥiq MSMEs with Qarḍ al-Ḥasan Products - Fatchurrohman, M.; Hadi, Nor; Takhim, Muhamad; Bahri, Saiful (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2024)
Law enforcement in zakāt compliance can increase the influence of social motivation. The existence of attitudes and subjective norms in exploring business owners and companies in the form of shares is also obliged to pay zakāt if it is fulfilled that profits continue and have reached ḥaul and niṣāb. This research is a study that uses an associative qualitative approach. Data analysis in this study uses the Spradley model, which begins with determining key informants. The implementation of shari’a stock zakāt distribution on mustaḥiq economic empowerment through the development of sustainable economic productivity in practice needs adjustments to shari’a economic law because the existence of soft financing without excess profit margins with a qarḍ al-ḥasan contract has become an alternative to financial inclusion. Therefore, it is necessary to implement alternative financial inclusion through Islamic zakāt shares to empower mustaḥiq MSMEs with qarḍ al-ḥasan products. Thus, law enforcement on zakāt collection can increase the distribution of zakāt that is right on target and sustainably utilized by mustaḥiq.